Contributions of CaV1.3 Channels to Ca2+ Current and Ca2+-Activated BK Current in the Suprachiasmatic Nucleus - McNally, Beth A.; Plante, Amber E.; Meredith, Andrea L. (Frontiers in Physiology, 2021)
Daily regulation of Ca2+- and voltage-activated BK K+ channel activity is required for action potential rhythmicity in the suprachiasmatic nucleus (SCN) of the hypothalamus, the brain’s circadian clock. In SCN neurons, BK activation is dependent upon multiple types of Ca2+ channels in a circadian manner. Daytime BK current predominantly requires Ca2+ influx through L-type Ca2+ channels (LTCCs), a time when BK channels are closely coupled with their Ca2+ source. Here we show that daytime BK current is resistant to the Ca2+ chelator BAPTA. However, at night when LTCCs contribute little to BK activation, BK current decreases by a third in BAPTA compared to control EGTA conditions. In phase with this time-of-day specific effect on BK current activation, LTCC current is larger during the day. The specific Ca2+ channel subtypes underlying the LTCC current in SCN, as well as the subtypes contributing the Ca2+ influx relevant for BK current activation, have not been identified. SCN neurons express two LTCC subtypes, CaV1.2 and CaV1.3. While a role for CaV1.2 channels has been identified during the night, CaV1.3 channel modulation has also been suggested to contribute to daytime SCN action potential activity, as well as subthreshold Ca2+ oscillations. Here we characterize the role of CaV1.3 channels in LTCC and BK current activation in SCN neurons using a global deletion of CACNA1D in mouse (CaV1.3 KO). CaV1.3 KO SCN neurons had a 50% reduction in the daytime LTCC current, but not total Ca2+ current, with no difference in Ca2+ current levels at night. During the day, CaV1.3 KO neurons exhibited oscillations in membrane potential, and most neurons, although not all, also had BK currents. Changes in BK current activation were only detectable at the highest voltage tested. These data show that while CaV1.3 channels contribute to the daytime Ca2+ current, this does not translate into a major effect on the daytime BK current. These data suggest that BK current activation does not absolutely require CaV1.3 channels and may therefore also depend on other LTCC subtypes, such as CaV1.2.